SOSIODEMOGRAPHIC FACTORS ON CONTRACEPTIVE USE AMONG MARRIED WOMAN: EVIDENCE FROM THREE INDONESIA DEMOGRAPHIC AND HEALTH SURVEY (IDHS) - Latifah, Nur Faridah; Jayanti, Ratna Dwi; Hardianto, Gatut (UNIVERSITAS AIRLANGGA, 2024)
Background: Data on contraceptive use are needed to evaluate contraceptive use and plan for future needs. Changes in contraceptive method use and the factors that influence contraceptive method use are serious matters that need to be considered. Methods: This study used secondary data from the Indonesian Demographic and Health Survey (IDHS) in 2007, 2012, and 2017. The research design used was cross-sectional. Researchers used descriptive analysis to determine the characteristics of married women who use contraception. Inferential analysis was used to see the relationship between sociodemographic factors and the use of contraceptive method types. Results: The results of the analysis showed that the most widely used type of contraception from 2007-2017 was injectable contraception. Most married women who used contraceptives were in the age group of 30-39 years, had only 1-2 children, had a high school education and below, and worked as housewives. Women living in rural and urban areas have equal opportunities to obtain contraceptive services. Even women with the lowest wealth index still have access to contraceptives. The chi-square test results of age, education, occupation, residence, and wealth index variables with p = 0.000 (p < 0.005) from 2007-2017, as well as the variable number of children with p = 0.000 (p < 0.005) in 2007, p = 0.002 (p < 0.005) in 2012 and p = 0.000 (p < 0.005) in 2017. Conclusion: This study found a positive association between contraceptive method use and the variables of age, education, occupation, number of children, place of residence, and wealth index.